(untitled) (Semiárida, 2019)
The production of ethanol from grain sorghum was investigated in the present work, in response to the need of exploring other materials to obtain alcohol by fermentation. A laboratory experimental protocol was designed in order to evaluate ethanol yield, from grain in 7 genotypes. The ethanol production varied from 428,13 to 481,5 ml.kg MS1 at 68 hours of fermentation. INTA Blanco and Antel INTA genotypes significantly differed in ethanol yield. Through this research it was not possible to determine the impact of particular grain properties on bioconversion. The high ethanol yield demonstrated that grain sorghum can be an alternative for different regions, since it is a crop that adapts to different soil types and climate.